John Rawls’ ‘justice as fairness’ and the demandingness problem - Victor Cruz e Silva (Acta Scientiarum. Human and Social Sciences, 2019)
John Rawls (1921-2002) was a liberal philosopher whose theory was, in the mid-twentieth century, the default mainstream political philosophy. His main theoretical construct is called justice as fairness. This study departs from the perception that there is an unexplored internal ethical tension within Rawls’ justice as fairness. We argue that Rawls’ deontological compass jeopardizes his reconciliation of liberalism and egalitarianism. Our objective is, accordingly, to elucidate the demandingness problem related to deontological ethics and how this affects Rawls’ ideal endeavors. This so-called demandingness problem was originally conceived in reference to consequentialist ethics. Accordingly, the alleged tension within Rawls’ system will be briefly contrasted with the controversy regarding John Stuart Mill’s (1806-1873) system of political economy usually noticed by the literature, in which the demandingness beams from the necessarily consequentialist nature of utilitarianism. Our conclusion is that, whereas utilitarianism is necessarily consequentialist, and, therefore, demanding, Rawls’ system does not integrate inevitably demanding rules of behavior. It is Rawls’ deontological background that promotes the tension between liberalism and egalitarianism in his reasoning.